Design and Build Academic Information System at SMK KARTIKA 2 SURABAYA - Sukarno, Prayudi Suryo; Lusiani, Titik; Sagirani, Tri (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2018)
SMK Kartika 2 Surabaya an educational institution that was established since 1994, and has several processes that include new admissions activities, class divisions and homeroom, scheduling subjects, and management student value as a material for preparing the results of student studies. Processes that exist in SMK Kartika 2 Surabaya there are some problems such as the process of data management students, teachers, schedules, class divisions and homeroom, and processing student value. The number of data and limitations of the scheduling officer so it takes a long time in managing the existing data. The long process of managing the data has a direct impact on the performance of the administration department, employees/ teachers in school academic activities. Solutions that can be given to the above problems is the application of academic information system, is one solution that can help the administration, employees / teachers in managing student data, teachers, schedules, class divisions along with homeroom, processing student value and reporting to the head school. Creation of Web-based academic information system application. It is expected to conduct student data management activities, teacher data, schedules, class divisions and homeroom, and final value creation, making it easier for the administration to report to the principal.